Hypovitaminosis-D and sexual dysfunction - Samreen; Khan, M. Imran; Saxena, Archna; Chakraborty, Rajarshi (International Journal of Advances in Medicine, 2024)
Sex has a significant impact on a person’s quality of life. Numerous elements, including endocrine, vascular, psychological, and neurological ones, have an impact on sexual function. Male and female sexual dysfunction is a prevalent issue in both sexes. About 30% of males and 40% of women are reported to have sexual dysfunction. The main factors influencing sexual responsiveness are neurological and endocrine activity. An increased risk of obstetric and gynecologic issues, including endometriosis, polycystic ovaries, infertility, gestational diabetes, preeclampsia, and ovarian and breast cancer, is also linked to vitamin-D insufficiency. Data from several studies conducted worldwide indicate that vitamin D is vital for both male and female sexual function.